The Development of Geogebra Augmented Reality-Assisted Contextual Teaching Material to Improve Creative Thinking Skills - Sa'aduddin; Anik Yuliani ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
The rapid development of digital technology has opened up opportunities to integrate innovative media into mathematics learning, particularly geometry, where students often struggle with spatial visualization and creative problem-solving. Conventional learning materials are often insufficient to stimulate student engagement and creative thinking. This study aims to develop contextual-based teaching materials assisted by GeoGebra Augmented Reality (AR) to enhance students' mathematical creative thinking skills. This study uses a Research and Development (R&D) approach with the ADDIE model. In the analysis phase, students' difficulties in understanding spatial figures and their low creative thinking performance were identified. The design phase produced a contextual framework supported by AR visualizations that aligned with the learning objectives. During the development phase, GeoGebra AR was integrated into the materials to create interactive and easily manipulated representations of polyhedra. The implementation phase involved limited and large-scale trials with Grade VIII students of SMP Pasundan 1 Cimahi. In the evaluation phase, expert validation and student response data were analyzed to determine the validity, practicality, and effectiveness of the developed product. The findings indicate that this teaching material is highly valid, as demonstrated by evaluations from material experts and ICT experts. Student responses in both trial phases also demonstrated a high level of practicality and positive acceptance. Furthermore, this teaching material proved highly effective in improving students' mathematical creative thinking skills, achieving an effectiveness rate of 96%. It can be concluded that the contextual teaching material assisted by GeoGebra AR developed in this study can support teachers in creating innovative, engaging, and conceptually meaningful learning experiences for students.